ANTIGUAS POSESIONES. LA MEMORIA DE BORGES Y LA CARA DE SHAKESPEARE - D'Angelo, Biagio (2005)
Borges represents ofmemory going back toa large web ofwriters who alsoappeal to recalling, in poetic texts once and again «reinstalled» and«contextualized». Borges' favorite recurrent face is Shakespeare's. Thisarticle is intended to unveil sorne reasons for this preference.